Maoist Combatants’ Narratives: Partisan Attachment to Post-truce Politics - Acharya, Khangendra (Literary Studies, 2020)
Ten-year long war led by Communist Party of Nepal (Maoist) [hereafter CPN (M)] from February 1996 to November 2006 has been understood as one of the most violent times in Nepali history. The armed wing of CPN (M), People’s Liberation Army (PLA) formed in 2001, was the armed group combating in the war front. Prior to the formation of PLA, CPN (M) had set up its armed groups differently: they had three-tier structure in 1994 that comprised combatant group, security group and volunteer group, which was transformed in 1997 into Guerrilla Squad, and in 1997 into Guerrilla Platoon. Subsequent transformations were Guerrilla Company in 1999 and Guerilla Battalion in 2000. All these groups were involved in armed actions of various magnitudes including selected annihilation, sabotage, ambush, raids and attacks.When the peace truce, the Comprehensive Peace Agreement (CPA), was agreed, CPN (M) claimed that the party had 32,000 People’s Liberation Army members, around 20,000 of whom were verified by the United Nations (UN).